Social Mobility, Health and Wellbeing in Poland - Zelinska, Olga; Gugushvili, Alexi; Bulczak, Grzegorz (Frontiers in Sociology, 2021)
Recently there has been a surge of interest in the consequences of intergenerational social mobility on individuals’ health and wellbeing outcomes. However, studies on the effects of social mobility on health, using high-quality panel survey data, have almost exclusively been conducted in Western welfare democracies. To account for this gap, and using empirical data from one of the largest and most eventful post-communist countries, Poland, in this study we investigate how individuals’ origin and destination socio-economic position and social mobility are linked to self-rated health and reported psychological wellbeing. We use the Polish Panel Survey (POLPAN) data to construct self-rated health and psychological wellbeing measures, origin, destination and occupational class mobility variables, and account for an extensive set of sociodemographic determinants of health. We employ diagonal reference models to distinguish social mobility effects from origin and destination effects, and account for possible health selection mechanisms. Our results suggest that there is an occupational class gradient in health in Poland and that both parental and own occupational class matter for individual health outcomes. We also find a positive reported psychological wellbeing effect for upward social mobility from the working to the professional class.